Safety evaluation of Avicenna germinans leaf extracts in rats - Kazeem Akinyinka Akinwumi; Oluwole Olusoji Eleyowo; Afeez Adeniyi Adesina; Theophilus Aghogho Jarikre; Eniola Deborah Adebayo; Zainab Adenike Oyekola (Elsevier, 2024)
Background: Avicenna germinans is one of Nigeria's dominant mangrove plants and has valuable pharmacological and therapeutic activity. It is widely employed in traditional medicine to treat many ailments and diseases, including cancer. However, little is known about the safety of the plant. Acute and sub-acute toxicity profiles of the plant extracts were assessed in this study. Methods: The oral acute toxicity was determined with 5000 mg/kg body weight each of n-hexane, ethyl acetate, and ethanol extracts of Avicenna germinans leaf in rats. The rats were monitored for mortality, clinical manifestations, and weight changes over 14 days. During the sub-acute toxicity study, twenty-five female rats were fed with 0-1000 mg/kg ethanol extracts of Avicenna germinans for 21 days. The body weight was monitored during treatment, while changes in gross organ morphology, relative organ weights, hematology, serum biochemistry, and limited histological analysis were evaluated after treatment. Results: Acute administration of the three extracts did not result in mortality or any obvious adverse effects. The gross pathology, relative organ weights, hematology, serum biochemistry, and histopathology were similar to the control, except for the 1000 mg/kg dose that evoked marked increases in relative heart, intestinal, thymus, and adrenal weights. In addition, foci of inflammatory cells in the interstitium and lymphoid hyperplasia were found in the heart and lungs, respectively, in the 1000 mg/kg group. Conclusion: The findings indicate that LD50 of the three extracts of Avicenna germinans were > 5000 mg/kg and sub-acute administration of the ethanol extract is relatively safe at least up to 750 mg/kg body weights.